Carbon-ceramic composite nanofiltration membrane as well as preparation method and application thereof

By using a combination of silicon oxide, titanium oxide, zirconium oxide and water-soluble lignin derivatives, a carbon-ceramic composite nanofiltration membrane was prepared, which solved the compatibility and flux problems of traditional ceramic nanofiltration membranes and carbon molecular sieve membranes, and achieved a carbon-ceramic composite nanofiltration membrane with high flux and high interception performance.

CN120618274APending Publication Date: 2025-09-12ZHEJIANG TIANXINGJIAN WATER SERVICE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510933002.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-07
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

Traditional ceramic nanofiltration membranes have problems such as large pore size distribution and poor retention performance. In addition, carbon molecular sieve membranes have low membrane flux in liquid separation. Commonly used raw materials have poor compatibility with ceramic membrane sol systems, resulting in incomplete membrane formation.

Method used

Silicon oxide, titanium oxide and zirconium oxide are used as oxide precursors, combined with water-soluble lignin derivatives, and SiO2-TiO2-ZrO2 sol is formed through hydrolysis and condensation reaction. After adding film-forming agents and lignin derivatives, a film is formed on the base membrane and sintered to form a carbon-ceramic composite nanofiltration membrane.

Benefits of technology

The membrane layer is flat, the pore size is uniform, the flux and the interception performance are high, the membrane flux and the interception performance are improved, the compatibility problem is solved, and a stable carbon-ceramic composite nanofiltration membrane is formed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120618274A_ABST
    Figure CN120618274A_ABST
Patent Text Reader

Abstract

The invention provides a carbon-ceramic composite nanofiltration membrane as well as a preparation method and application thereof, and relates to the technical field of inorganic nanofiltration membranes. The carbon-ceramic composite nanofiltration membrane provided by the invention is prepared from the following preparation raw materials in parts by mass: 5 to 30 parts of an oxide precursor, 10 to 50 parts of an alcohol solvent, 1 to 35 parts of water, 0.04 to 0.5 part of an acid catalyst, 0.1 to 2 parts of a film-forming agent and 0.1 to 4 parts of a water-soluble lignin derivative, the oxide precursor comprises a silicon oxide precursor, a titanium oxide precursor and a zirconium oxide precursor, the mass ratio of the silicon oxide precursor to the titanium oxide precursor to the zirconium oxide precursor is (0-10): (0-20): (0-9), and the mass of each precursor is not 0. The carbon-ceramic composite nanofiltration membrane provided by the invention has the advantages of flat membrane layer, uniform pore diameter, high flux and high closure, is firmly combined with a matrix, and is suitable for market popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of inorganic nanofiltration membranes, and in particular to a carbon-ceramic composite nanofiltration membrane and a preparation method and application thereof. Background Art

[0002] Ceramic membranes hold great promise in water treatment due to their resistance to contamination, high permeability, good recyclability, chemical stability, and long service life. However, as water quality requirements continue to rise, traditional ultrafiltration ceramic membranes are no longer able to meet these requirements, particularly for the separation of small molecular weight pollutants. Consequently, market demand for nanofiltration ceramic membranes continues to rise. While nanofiltration ceramic membranes offer improved performance compared to ultrafiltration ceramic membranes, they generally suffer from a wide pore size distribution and poor retention.

[0003] Carbon molecular sieve membranes (CMS) are typically made by pyrolysis of organic precursors (such as amorphous polymers). Composed of rigid units, CMS is harder and has a smaller carbonization expansion volume than its polymer precursors. CMS pores are small (a few angstroms) and have a narrow distribution, enabling molecular-level separations through size sieving. However, CMS is affected by multiple factors, including liquid viscosity, surface tension, and chemical interactions, often resulting in low membrane flux in liquid separations.

[0004] The combination of ceramics and carbon molecular sieves is expected to complement each other's weaknesses and balance the optimization of their retention and flux performance. However, the raw materials commonly used to prepare carbon molecular sieve membranes, such as phenolic resin and graphene oxide, are poorly compatible with traditional nanofiltration ceramic membrane sol systems. During the precursor preparation process, phase separation and agglomeration are prone to occur, interfering with the carbonization and sintering process, resulting in the inability to form a structurally complete membrane material. This problem has long been a difficult obstacle to overcome in this field. Summary of the Invention

[0005] In view of this, the object of the present invention is to provide a carbon-ceramic composite nanofiltration membrane and its preparation method and application. The carbon-ceramic composite nanofiltration membrane provided by the present invention has a flat membrane layer while having high flux and high interception performance.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a carbon-ceramic composite nanofiltration membrane, comprising the following raw materials in parts by weight:

[0008] 5-30 parts of oxide precursor, 10-50 parts of alcohol solvent, 1-35 parts of water, 0.04-0.5 parts of acid catalyst, 0.1-2 parts of film-forming agent, 0.1-4 parts of water-soluble lignin derivative;

[0009] The oxide precursors include a silicon oxide precursor, a titanium oxide precursor and a zirconium oxide precursor, the mass ratio of the silicon oxide precursor, the titanium oxide precursor and the zirconium oxide precursor is (0-10):(0-20):(0-9), and the masses of the silicon oxide precursor, the titanium oxide precursor and the zirconium oxide precursor are not 0.

[0010] Preferably, the mass ratio of the silicon oxide precursor, the titanium oxide precursor and the zirconium oxide precursor is (2-8.5):(2-15):(0.5-7).

[0011] Preferably, the silicon oxide precursor includes one or more of tetraethyl orthosilicate, tetramethyl orthosilicate, silica sol and sodium silicate, the titanium oxide precursor includes one or more of tetrabutyl titanate, tetraethyl titanate, tetraisopropyl titanate and titanium tetrachloride, and the zirconium oxide precursor includes one or more of zirconium n-butoxide, tetrabutyl zirconate, zirconium oxychloride and zirconium sulfate.

[0012] Preferably, the alcohol solvent includes one or more of methanol, ethanol, isopropanol and n-butanol.

[0013] Preferably, the acid catalyst includes one or more of acetic acid, hydrochloric acid, nitric acid and benzoic acid.

[0014] Preferably, the film-forming agent comprises one or more of hydroxymethyl cellulose, polyvinyl alcohol, polyethylene glycol and polyvinyl pyrrolidone.

[0015] Preferably, the water-soluble lignin derivative includes one or more of lignin phenol, lignin sulfonate and lignin acid ester; the lignin phenol includes one or more of guaiacol, eugenol and catechol; the lignin sulfonate includes sodium lignin sulfonate and / or potassium lignin sulfonate; the lignin acid ester includes one or more of lignin sulfonate, lignin acetate and lignin oxalate.

[0016] The present invention provides a method for preparing the carbon-ceramic composite nanofiltration membrane described in the above technical solution, comprising the following steps:

[0017] The oxide precursor, alcohol solvent and water are mixed to undergo a hydrolysis reaction to obtain a SiO2-TiO2-ZrO2 sol suspension;

[0018] The SiO2-TiO2-ZrO2 sol suspension is mixed with an acid catalyst to carry out a polycondensation reaction, and the obtained polycondensation reaction liquid is mixed with a film-forming agent and a water-soluble lignin derivative and aged to obtain a sol mixed suspension;

[0019] forming a film of the sol mixed suspension on a base membrane and then drying the film to obtain a sol composite ceramic nanofiltration membrane embryo;

[0020] The sol-composite ceramic nanofiltration membrane embryo is sintered to obtain the carbon-ceramic composite nanofiltration membrane.

[0021] Preferably, the hydrolysis reaction time is 1 to 5 hours; the polycondensation reaction time is 1 to 12 hours; the aging time is 5 to 24 hours; the sintering temperature is 300 to 1000°C, and the time is 1 to 10 hours. The sintering atmosphere includes oxygen and nitrogen, and the volume ratio of oxygen to nitrogen is (0 to 2): (8 to 10).

[0022] The present invention provides the use of the carbon-ceramic composite nanofiltration membrane described in the above technical solution or the carbon-ceramic composite nanofiltration membrane prepared by the preparation method described in the above technical solution in liquid separation or water pollutant treatment.

[0023] The present invention provides a carbon-ceramic composite nanofiltration membrane, comprising the following raw materials in parts by weight: 5 to 30 parts of an oxide precursor, 10 to 50 parts of an alcohol solvent, 1 to 35 parts of water, 0.04 to 0.5 parts of an acid catalyst, 0.1 to 2 parts of a film-forming agent, and 0.1 to 4 parts of a water-soluble lignin derivative; the oxide precursor comprises a silicon oxide precursor, a titanium oxide precursor, and a zirconium oxide precursor, and the mass ratio of the silicon oxide precursor, the titanium oxide precursor, and the zirconium oxide precursor is (0 to 10):(0 to 20):(0 to 9), and the masses of the silicon oxide precursor, the titanium oxide precursor, and the zirconium oxide precursor are all non-zero. Compared with the prior art, the present invention has the following beneficial effects:

[0024] The water-soluble lignin derivative of the present invention has excellent hydrophilicity and good compatibility with the oxide sol system, and can form a uniform and stable suspension, thereby preventing subsequent film formation and agglomeration and phase separation during the drying process during the preparation process, and promoting the integrity and uniformity of the morphology of the membrane material after sintering. On the other hand, as a carbon source, it has a chemical structure of multiple benzene rings. During the carbonization process, bonding and rearrangement occur between carbon atoms, and aggregation forms a highly ordered layered graphite or graphene structure, forming a carbon layer with a molecular-level pore size, thereby improving the retention performance of the material and optimizing the pore size and pore size uniformity of the carbon-ceramic composite nanofiltration membrane.

[0025] The present invention uses silicon oxide precursors, titanium oxide precursors, and zirconium oxide precursors as oxide precursors. Hydrolysis and condensation form an oxide sol, which boasts a uniform particle size distribution and small nanometer size. Therefore, when used as a ceramic precursor for the separation layer of a nanofiltration membrane, sintering allows for the close aggregation and cohesion of the nanosol particles, ultimately forming a ceramic membrane with a small pore size. Furthermore, the excellent hydrophilicity of the resulting oxide sol ensures high flux for the carbon-ceramic composite nanofiltration membrane.

[0026] The carbon-ceramic composite nanofiltration membrane provided by the present invention has the advantages of smooth membrane layer, uniform pore size, high flux and high interception, and is firmly bonded to the substrate, and is suitable for market promotion and application.

[0027] The results of the examples show that the carbon-ceramic composite nanofiltration provided by the present invention not only has a high membrane flux, with a pure water flux of up to 12.3LMH / bar, but also has excellent retention performance, with a MgSO4 retention rate of up to 99.6%. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 Scanning electron microscope images of the carbon-ceramic composite nanofiltration membrane prepared in Example 3, the pure ceramic nanofiltration membrane prepared in Comparative Example 1, and the base membrane without any treatment;

[0029] Figure 2 The carbon-ceramic composite nanofiltration membrane prepared in Example 3 ( Figure 2 Digital photos of the carbon-ceramic membrane in the image) and the base membrane without any treatment;

[0030] Figure 3 The carbon-ceramic composite nanofiltration membrane prepared in Example 3 ( Figure 3 Digital photos of the exudate of cresol red sodium salt in aqueous solution separated by the pure ceramic nanofiltration membrane prepared in Comparative Example 1, the carbon molecular sieve nanofiltration membrane prepared in Comparative Example 2, and the basement membrane without any treatment;

[0031] Figure 4 These are the performance curves for separating MgSO4 from aqueous solution using the carbon-ceramic composite nanofiltration membrane prepared in Example 3, the pure ceramic nanofiltration membrane prepared in Comparative Example 1, and the carbon molecular sieve nanofiltration membrane prepared in Comparative Example 2. DETAILED DESCRIPTION

[0032] The present invention provides a carbon-ceramic composite nanofiltration membrane, comprising the following raw materials in parts by weight:

[0033] 5-30 parts of oxide precursor, 10-50 parts of alcohol solvent, 1-35 parts of water, 0.04-0.5 parts of acid catalyst, 0.1-2 parts of film-forming agent, 0.1-4 parts of water-soluble lignin derivative;

[0034] The oxide precursors include a silicon oxide precursor, a titanium oxide precursor and a zirconium oxide precursor, the mass ratio of the silicon oxide precursor, the titanium oxide precursor and the zirconium oxide precursor is (0-10):(0-20):(0-9), and the masses of the silicon oxide precursor, the titanium oxide precursor and the zirconium oxide precursor are not 0.

[0035] In the present invention, unless otherwise specified, all raw materials involved are commercially available products well known in the art.

[0036] The carbon-ceramic composite nanofiltration membrane provided by the present invention comprises 5 to 30 parts by mass of an oxide precursor, which may be 5, 10, 11, 15, 18, 19, 20, 21, 25, 29 or 30 parts. In the present invention, the oxide precursor comprises a silicon oxide precursor, a titanium oxide precursor and a zirconium oxide precursor. The silicon oxide precursor preferably comprises one or more of tetraethyl orthosilicate, tetramethyl orthosilicate, silica sol and sodium silicate. The titanium oxide precursor preferably comprises one or more of tetrabutyl titanate, tetraethyl titanate, tetraisopropyl titanate and titanium tetrachloride. The zirconium oxide precursor preferably comprises one or more of zirconium n-butoxide, tetrabutyl zirconate, zirconium oxychloride and zirconium sulfate. In the present invention, the mass ratio of the silicon oxide precursor, titanium oxide precursor and zirconium oxide precursor is (0-10): (0-20): (0-9) (the masses of the silicon oxide precursor, titanium oxide precursor and zirconium oxide precursor are not 0), preferably (2-8.5): (2-15): (0.5-7), and more preferably (2-6): (2-12): (2-6.5). The present invention adopts three oxide precursors of silicon oxide precursor, titanium oxide precursor and zirconium oxide precursor, wherein after the silicon oxide precursor and titanium oxide precursor are completely hydrolyzed, Ti-O-Si bonds are formed through condensation reaction, and zirconium ions exist in the network gaps. The ceramic film formed has high mechanical strength and stable structure.

[0037] The carbon-ceramic composite nanofiltration membrane provided by the present invention includes 10 to 50 parts of an alcohol solvent, based on the mass fraction of the oxide precursor, and can be 10, 15, 18, 20, 24, 25, 30, 33, 35, 40, 42, 45, or 50 parts. In the present invention, the alcohol solvent preferably includes one or more of methanol, ethanol, isopropanol, and n-butanol.

[0038] The carbon-ceramic composite nanofiltration membrane provided by the present invention includes 1 to 35 parts of water, based on the mass fraction of the oxide precursor, which can be 1, 5, 10, 15, 16, 20, 22, 23, 25, 30, or 35 parts. In the present invention, the alcohol solvent and water provide a hydrolysis environment for the silicon oxide precursor, the titanium oxide precursor, and the zirconium oxide precursor, wherein the type of alcohol solvent affects the hydrolysis rate of the oxide precursor.

[0039] Based on the mass fraction of the oxide precursor, the carbon-ceramic composite nanofiltration membrane provided by the present invention includes 0.04 to 0.5 parts of an acid catalyst, which can be 0.1, 0.2, 0.3, 0.4 or 0.5 parts. In the present invention, the acid catalyst preferably includes one or more of acetic acid, hydrochloric acid, nitric acid and benzoic acid. In an embodiment of the present invention, the mass fraction of the acetic acid is 99.5%, the mass fraction of the hydrochloric acid is 37.5%, the mass fraction of the nitric acid is 64%, and the mass fraction of the benzoic acid is 99.5%. In the present invention, the introduction of the acid catalyst can form an acidic environment, inducing and promoting the hydrolysis and condensation of the oxide precursor.

[0040] Based on the mass fraction of the oxide precursor, the carbon-ceramic composite nanofiltration membrane provided by the present invention includes 0.1 to 2 parts of a film-forming agent, which can be 0.1, 0.3, 0.4, 0.5, 0.6, 0.8, 1, 1.1, 1.4, 1.5, 1.6 or 2 parts. In the present invention, the film-forming agent preferably includes one or more of hydroxymethyl cellulose, polyvinyl alcohol, polyethylene glycol and polyvinyl pyrrolidone. In an embodiment of the present invention, the molecular weight of the hydroxymethyl cellulose is 90,000, the molecular weight of the polyvinyl alcohol is 27,000, the molecular weight of the polyvinyl pyrrolidone is 58,000, and the molecular weight of the polyethylene glycol is 400. In the present invention, the addition of the film-forming agent can ensure the molding of the composite ceramic nanofiltration membrane embryo, and the film-forming agent can also play a role in adjusting the thermal expansion coefficient.

[0041] Based on the mass fraction of the oxide precursor, the carbon-ceramic composite nanofiltration membrane provided by the present invention includes 0.1 to 4 parts of a water-soluble lignin derivative, which can be 0.1, 0.4, 0.5, 1, 1.2, 1.5, 1.7, 2, 3 or 4 parts. In the present invention, the water-soluble lignin derivative preferably includes one or more of lignin phenol, lignin sulfonate and lignin acid ester; the lignin phenol preferably includes one or more of guaiacol, eugenol (3-acetyl-4-hydroxyphenol) and catechol, and the lignin phenol has a uniform molecular weight, which is beneficial to the pore size control of the carbon membrane material; the lignin sulfonate preferably includes sodium lignin sulfonate and / or potassium lignin sulfonate. In an embodiment of the present invention, the molecular weight of the sodium lignin sulfonate is 52,000, and the molecular weight of the potassium lignin sulfonate is 5,000 to 10,000; the lignin acid ester preferably includes one or more of lignin sulfonate, lignin acetate and lignin oxalate. In an embodiment of the present invention, the molecular weight of the lignin sulfonate is 20,000, the molecular weight of the lignin acetate is 15,000 to 18,000, and the molecular weight of the lignin oxalate is 30,000. In an embodiment of the present invention, the water-soluble lignin derivative is a mixture of guaiacol and potassium lignin sulfonate, wherein the mass ratio of guaiacol to potassium lignin sulfonate is 1:2.6; or, the water-soluble lignin derivative is a mixture of guaiacol, sodium lignin sulfonate and lignin sulfonate, wherein the mass ratio of guaiacol, sodium lignin sulfonate and lignin sulfonate is 1:0.28:0.14; or, the water-soluble lignin derivative is a mixture of eugenol, potassium lignin sulfonate and lignin oxalate, wherein the mass ratio of guaiacol, sodium lignin sulfonate and lignin sulfonate is 1:0.28:0.14. The mass ratio of potassium sulfonate and lignin oxalate is 1:1:1; or, the water-soluble lignin derivative is a mixture of potassium lignin sulfonate and lignin sulfonate, wherein the mass ratio of potassium lignin sulfonate to lignin sulfonate is 1:3; or, the water-soluble lignin derivative is a mixture of eugenol and lignin acetate, wherein the mass ratio of eugenol to lignin acetate is 1:1; or, the water-soluble lignin derivative is a mixture of catechol and sodium lignin sulfonate, wherein the mass ratio of catechol to sodium lignin sulfonate is 1:7.5. In the present invention, the water-soluble lignin derivative is a derivative directly modified from lignin, has strong solubility, and has good compatibility (or affinity) with the sol system formed by the oxide precursor. It can jointly construct a uniform and dense polymer network with the film-forming agent. The lignin structure has a multi-benzene ring structure, and after carbonization, it can form a uniform and dense carbon film, further controlling and optimizing the pore size and pore size uniformity of the carbon-ceramic composite nanofiltration membrane. In addition, the water-soluble lignin derivative is inexpensive and easily available.

[0042] The present invention solves the compatibility problem of ceramic nanofiltration membranes and carbon molecular sieve nanofiltration membranes by compounding a sol formed by a water-soluble lignin derivative with a silicon oxide precursor, a titanium oxide precursor and a zirconium oxide precursor, and solves the pain points and difficulties in this field. The carbon-ceramic composite nanofiltration membrane provided by the present invention has the advantages of smooth membrane layer, high flux, high interception, uniform pore size, and strong bonding with the substrate. The results of the examples show that compared with pure carbon nanofiltration membranes, the flux of the carbon-ceramic composite nanofiltration membrane provided by the present invention is greatly improved, which confirms the effect of the sol formed by the oxide precursor on the flux improvement of the carbon-ceramic composite nanofiltration membrane.

[0043] The present invention provides a method for preparing the carbon-ceramic composite nanofiltration membrane described in the above technical solution, comprising the following steps:

[0044] The oxide precursor, alcohol solvent and water are mixed to undergo a hydrolysis reaction to obtain a SiO2-TiO2-ZrO2 sol suspension;

[0045] The SiO2-TiO2-ZrO2 sol suspension is mixed with an acid catalyst to carry out a polycondensation reaction, and the obtained polycondensation reaction liquid is mixed with a film-forming agent and a water-soluble lignin derivative and aged to obtain a sol mixed suspension;

[0046] The lignin-SiO2-TiO2-ZrO2 sol mixed suspension is formed on the base film and then dried to obtain a sol composite ceramic nanofiltration membrane embryo;

[0047] The sol-composite ceramic nanofiltration membrane embryo is sintered to obtain the carbon-ceramic composite nanofiltration membrane.

[0048] The invention mixes an oxide precursor, an alcohol solvent and water to carry out a hydrolysis reaction to obtain a SiO2-TiO2-ZrO2 sol suspension.

[0049] In the present invention, the hydrolysis reaction time is preferably 1 to 5 hours, and can be 1, 2, 2.5, 3, 3.5, 4 or 5 hours. The hydrolysis reaction can be carried out at room temperature (i.e., without additional heating or cooling); the hydrolysis reaction is preferably carried out under stirring conditions.

[0050] After obtaining the SiO2-TiO2-ZrO2 sol suspension, the present invention mixes the SiO2-TiO2-ZrO2 sol suspension with an acid catalyst for polycondensation reaction, and mixes the obtained polycondensation reaction liquid with a film-forming agent and a water-soluble lignin derivative for aging to obtain a sol mixed suspension.

[0051] The present invention preferably adds an acid catalyst to the SiO2-TiO2-ZrO2 sol suspension; the pH value of the mixed system obtained by mixing the SiO2-TiO2-ZrO2 sol suspension and the acid catalyst is preferably 1 to 6, more preferably 2 to 5, and further preferably 2 to 4. In the present invention, the time of the polycondensation reaction is preferably 1 to 12 hours, and can be 2, 3, 3.5, 4, 5, 6, 7, 8, 9, 10, 11 or 12 hours; the polycondensation reaction can be carried out at room temperature (i.e., no additional heating or cooling is required); the polycondensation reaction is preferably carried out under stirring. In the present invention, after the silicon oxide precursor, zirconium oxide precursor and titanium oxide precursor are completely hydrolyzed, Ti-O-Si bonds are formed through polycondensation, and zirconium ions exist in the network gaps. The sol formed by hydrolysis and polycondensation has a uniform particle size distribution and a small nanometer size. In the present invention, the method for mixing the polycondensation reaction liquid with a film-forming agent and a water-soluble lignin derivative is preferably as follows: adding the film-forming agent and the water-soluble lignin derivative to the obtained polycondensation reaction liquid and stirring until completely dissolved. The resulting mixed liquid is recorded as a lignin-SiO2-TiO2-ZrO2 sol mixed suspension. In the present invention, the aging time is preferably 5 to 24 hours, and can be 6, 7, 7.5, 8, 8.5, 10, 12, 14, 15, 16, 18, 20, or 24 hours. The aging is carried out at room temperature (i.e., without additional heating or cooling) and under static conditions. During the aging process, the hydroxyl groups in the lignin derivative can react with the hydroxyl groups on the surface of the ceramic oxide through a condensation reaction to form Si-OC or Ti-OC bonds. In the present invention, the sol mixed suspension obtained after aging is recorded as a L-SiO2-TiO2-ZrO2 sol mixed suspension.

[0052] After aging to obtain a sol mixed suspension, the present invention forms a film of the sol mixed suspension on a base membrane and then dries it to obtain a sol composite ceramic nanofiltration membrane embryo.

[0053] The present invention has no particular requirements for the base membrane; any base membrane familiar to those skilled in the art can be used, and it can be a ceramic membrane. In the present invention, the membrane-forming method is preferably: immersing the base membrane in the sol-gel mixed suspension. In the present invention, the immersion time is preferably 20 to 400 seconds, and can be 40, 50, 60, 100, 110, 120, 140, 150, 160, 200, 300, or 400 seconds. Controlling the immersion time within the above range is beneficial for improving the bonding strength between the nanofiltration membrane and the base membrane while ensuring the membrane has an appropriate thickness, thereby avoiding adverse effects on flux. In the present invention, the drying temperature is preferably 30 to 70°C, and can be 35, 40, 45, 50, 55, 60, or 70°C. The drying time is preferably 1 to 5 days, and can be 1, 2, 3, 4, or 5 days. The present invention allows the solvent to evaporate slowly at the above drying temperature, which helps reduce the occurrence of nanofiltration membrane defects.

[0054] After obtaining the sol-composite ceramic nanofiltration membrane embryo, the present invention sintered the sol-composite ceramic nanofiltration membrane embryo to obtain the carbon-ceramic composite nanofiltration membrane.

[0055] In the present invention, the sintering temperature (also referred to as firing in the embodiments) is preferably 300-1000°C, and may be 400, 500, 600, 650, 700, 800, or 900°C. The heating rate from room temperature to the sintering temperature is preferably 0.5-5°C / min, and may be 0.5, 1, 2, 3, 4, or 5°C / min. The sintering time is preferably 1-10 hours, and may be 1, 2, 3, 4, 5, 6, 7, 8, or 9 hours. In the present invention, the sintering temperature affects ceramic molding and particle size, and affects parameters such as product strength, porosity, and molecular weight cut-off. In the present invention, the sintering atmosphere preferably includes oxygen and nitrogen, and the volume ratio of oxygen to nitrogen is preferably (0-2): (8-10). When the volume of oxygen is not 0, the volume ratio of oxygen to nitrogen is preferably (0.3-2): (8-9.7), which can be 0.3:9.7, 0.4:9.6, 0.5:9.5, 0.7:9.3, 0.8:9.2, 1.5:8.5 or 2:8; In the present invention, the oxygen will affect the sintering of ceramics and promote the decomposition of lignin derivatives to form carbon dioxide, which will in turn affect the porosity. In an embodiment of the present invention, the sintering is carried out in a tubular furnace. During the sintering process, the raw materials interact with each other to form stable chemical bonds, the gel state is converted into a ceramic state, and the lignin structure has a polyphenyl ring structure, which forms a uniform and dense carbon film after carbonization as a carbon source. After the sintering, a carbon-SiO2-TiO2-ZrO2 ceramic composite nanofiltration membrane is obtained, namely the carbon-ceramic composite nanofiltration membrane.

[0056] In the present invention, the thickness of the carbon-ceramic composite nanofiltration membrane is preferably 50 to 200 nm, the porosity is preferably 30 to 45%, and the molecular weight cut-off is preferably 200 to 500 Da, such as 400 Da.

[0057] The present invention provides the use of the carbon-ceramic composite nanofiltration membrane described in the above technical solution, or the carbon-ceramic composite nanofiltration membrane prepared by the preparation method described in the above technical solution, for liquid separation or water pollutant treatment. In the present invention, the liquid separation can be lithium extraction from salt lakes, pharmaceutical separation, etc.; in the embodiments of the present invention, the separation of MgSO4 in aqueous solution is used as an example. In the present invention, the pollutants are specifically low-molecular-weight pollutants; in the embodiments of the present invention, the treatment of sodium cresol red in aqueous solution is used as an example.

[0058] To further illustrate the present invention, the carbon-ceramic composite nanofiltration membrane provided by the present invention, its preparation method and application are described in detail below with reference to examples, but they should not be construed as limiting the scope of protection of the present invention.

[0059] Example 1

[0060] 4.12 g of tetraethyl orthosilicate, 2.03 g of tetrabutyl titanate, 4.28 g of zirconium n-butoxide, 42 g of methanol and 16 g of water were mixed and stirred for 1 h to hydrolyze to obtain a SiO2-TiO2-ZrO2 sol suspension; 0.04 g of acetic acid (mass fraction 99.5%) was added to the obtained SiO2-TiO2-ZrO2 sol suspension, the pH value was adjusted to 6, and the stirring was continued for 1 h, and then 2.00 g of hydroxymethyl cellulose (molecular weight 90000), 0.12 g of guaiacol and 0.31 g of potassium lignin sulfonate (molecular weight 5000-10000) were added and stirred until completely dissolved to obtain the lignin-SiO2-TiO2 -ZrO2 sol mixed suspension was allowed to stand and age for 24 hours, and the obtained mixed solution was recorded as L-SiO2-TiO2-ZrO2 sol mixed suspension; the ceramic membrane was placed in the obtained L-SiO2-TiO2-ZrO2 sol mixed suspension and immersed for 40 seconds, and then placed in a 70°C environment for 3 days to obtain a L-SiO2-TiO2-ZrO2 sol composite ceramic nanofiltration membrane embryo; the obtained L-SiO2-TiO2-ZrO2 sol composite ceramic nanofiltration membrane embryo was placed in a tubular furnace in an atmosphere with an oxygen to nitrogen volume ratio of 2:8, and the temperature was raised to 600°C at 0.5°C / min and fired for 1 hour to finally obtain a carbon-ceramic composite nanofiltration membrane.

[0061] Example 2

[0062] 4.12 g of tetraethyl orthosilicate, 20 g of tetrabutyl titanate, 5.11 g of zirconium n-butoxide, 50 g of ethanol and 35 g of water were mixed, stirred for 5 h, and hydrolyzed to obtain a SiO2-TiO2-ZrO2 sol suspension; 0.5 g of benzoic acid (mass fraction 99.5%) was added to the obtained SiO2-TiO2-ZrO2 sol suspension, the pH value was adjusted to 3, and the stirring was continued for 4 h, followed by the addition of 1.1 g of polyvinyl alcohol (molecular weight 27000), 1 g of guaiacol, 0.28 g of sodium lignin sulfonate (molecular weight 52000) and 0.14 g of lignin sulfonate (molecular weight 20000), and the mixture was stirred until it was completely dissolved. The obtained sol mixed suspension was allowed to stand and age for 5 hours, and the obtained mixed solution was recorded as L-SiO2-TiO2-ZrO2 sol mixed suspension; the ceramic membrane was placed in the obtained L-SiO2-TiO2-ZrO2 sol mixed suspension and immersed for 400 seconds, and then dried at 30°C for 5 days to obtain a L-SiO2-TiO2-ZrO2 sol composite ceramic nanofiltration membrane embryo; the obtained L-SiO2-TiO2-ZrO2 sol composite ceramic nanofiltration membrane embryo was placed in a tubular furnace under a nitrogen atmosphere, heated to 300°C at a rate of 2°C / min and fired for 10 hours to finally obtain a carbon-ceramic composite nanofiltration membrane.

[0063] Example 3

[0064] 2.3 g of tetraethyl orthosilicate, 5.6 g of tetrabutyl titanate, 2.1 g of zirconium n-butoxide, 33.2 g of methanol and 20 g of water were mixed, stirred for 3 h, and hydrolyzed to obtain a SiO2-TiO2-ZrO2 sol suspension; 0.1 g of hydrochloric acid (mass fraction 37.5%) was added to the obtained SiO2-TiO2-ZrO2 sol suspension, the pH value was adjusted to 4, and the stirring was continued for 2 h, followed by the addition of 0.6 g of hydroxymethyl cellulose (molecular weight 90,000), 0.4 g of eugenol, 0.4 g of potassium lignin sulfonate (molecular weight 5,000-10,000) and 0.4 g of lignin oxalate (molecular weight 30,000), and the mixture was stirred until completely dissolved. The obtained sol mixed suspension was allowed to stand and age for 12 hours, and the obtained mixed solution was recorded as L-SiO2-TiO2-ZrO2 sol mixed suspension; the ceramic membrane was placed in the obtained L-SiO2-TiO2-ZrO2 sol mixed suspension and soaked for 40 seconds, and then placed in a 40°C environment and dried for 3 days to obtain a L-SiO2-TiO2-ZrO2 sol composite ceramic nanofiltration membrane embryo; the obtained L-SiO2-TiO2-ZrO2 sol composite ceramic nanofiltration membrane embryo was placed in a tubular furnace in an atmosphere with an oxygen to nitrogen volume ratio of 0.3:9.7, and the temperature was raised to 700°C at 2°C / min and fired for 3 hours to finally obtain a carbon-ceramic composite nanofiltration membrane.

[0065] Example 4

[0066] 10g of tetraethyl orthosilicate, 5.6g of tetrabutyl titanate, 9g of zirconium n-butoxide, 24g of isopropanol and 15g of water were mixed, stirred for 3.5h, and hydrolyzed to obtain a SiO2-TiO2-ZrO2 sol suspension; 0.15g of acetic acid (mass fraction 99.5%) was added to the obtained SiO2-TiO2-ZrO2 sol suspension, the pH value was adjusted to 1, and stirring was continued for 12h, and then 0.8g of polyvinyl pyrrolidone (molecular weight 58000), 2g of eugenol, and 2g of lignin acetate (molecular weight 15000-18000) were added, and stirred until completely dissolved. The obtained sol mixed suspension was allowed to stand for aging. The mixture was precipitated for 16 hours, and the obtained mixed solution was recorded as L-SiO2-TiO2-ZrO2 sol mixed suspension; the ceramic membrane was placed in the obtained L-SiO2-TiO2-ZrO2 sol mixed suspension and immersed for 20 seconds, and then dried in an environment of 60°C for 1 day to obtain a L-SiO2-TiO2-ZrO2 sol composite ceramic nanofiltration membrane embryo; the obtained L-SiO2-TiO2-ZrO2 sol composite ceramic nanofiltration membrane embryo was placed in a tubular furnace in an atmosphere with an oxygen to nitrogen ratio of 1.5:8.5 by volume, and the temperature was raised to 1000°C at 1°C / min and fired for 6 hours to finally obtain a carbon-ceramic composite nanofiltration membrane.

[0067] Example 5

[0068] 5.1 g of tetraethyl orthosilicate, 5.6 g of tetrabutyl titanate, 8.4 g of zirconium n-butoxide, 24 g of n-butanol, and 15 g of water were mixed and stirred for 3.5 h to hydrolyze to obtain a SiO2-TiO2-ZrO2 sol suspension. 0.15 g of hydrochloric acid (mass fraction 37.5%) was added to the obtained SiO2-TiO2-ZrO2 sol suspension to adjust the pH to 1. The suspension was stirred for 12 h. 0.8 g of polyethylene glycol (molecular weight 400), 0.2 g of catechol, and 1.5 g of sodium lignin sulfonate (molecular weight 52000) were then added and stirred until completely dissolved. The obtained suspension was allowed to stand for 7 days. 5h, and the obtained mixed liquid is recorded as L-SiO2-TiO2-ZrO2 sol mixed suspension; the ceramic membrane is placed in the obtained L-SiO2-TiO2-ZrO2 sol mixed suspension and immersed for 120s, and then placed in a 55℃ environment for drying for 3 days to obtain a L-SiO2-TiO2-ZrO2 sol composite ceramic nanofiltration membrane embryo; the obtained L-SiO2-TiO2-ZrO2 sol composite ceramic nanofiltration membrane embryo is placed in a tubular furnace in an atmosphere with an oxygen to nitrogen volume ratio of 0.7:9.3, and the temperature is increased at 5℃ / min to 600℃ for 4h to obtain a carbon-ceramic composite nanofiltration membrane.

[0069] Example 6

[0070] 4.3 g of tetraethyl orthosilicate, 8.4 g of tetrabutyl titanate, 2.24 g of zirconium n-butoxide, 10 g of ethanol and 1 g of water were mixed, stirred for 2.5 h, and hydrolyzed to obtain a SiO2-TiO2-ZrO2 sol suspension; 0.25 g of nitric acid (mass fraction 64%) was added to the obtained SiO2-TiO2-ZrO2 sol suspension, the pH value was adjusted to 6, and the stirring was continued for 4 h, followed by the addition of 0.3 g of hydroxymethyl cellulose (molecular weight 90,000) and 0.1 g of polyethylene glycol (molecular weight 400), 0.5 g of potassium lignin sulfonate (molecular weight 5,000-10,000) and 1.5 g of lignin sulfonate (molecular weight 20,000), and the mixture was stirred until completely dissolved. The obtained sol mixed suspension was allowed to stand and age for 8.5 hours, and the obtained mixed solution was recorded as L-SiO2-TiO2-ZrO2 sol mixed suspension; the ceramic membrane was placed in the obtained L-SiO2-TiO2-ZrO2 sol mixed suspension and immersed for 160 seconds, and then dried in a 45°C environment for 4 days to obtain a L-SiO2-TiO2-ZrO2 sol composite ceramic nanofiltration membrane embryo; the obtained L-SiO2-TiO2-ZrO2 sol composite ceramic nanofiltration membrane embryo was placed in a tubular furnace in an atmosphere with an oxygen to nitrogen volume ratio of 0.5:9.5, and the temperature was raised to 800°C at 2°C / min and fired for 3 hours to finally obtain a carbon-ceramic composite nanofiltration membrane.

[0071] Example 7

[0072] 8.3g of tetraethyl orthosilicate, 10.4g of tetrabutyl titanate, 2.24g of zirconium n-butoxide, 18g of ethanol and 16g of water were mixed, stirred for 3.5h, and hydrolyzed to obtain a SiO2-TiO2 sol suspension; 0.25g of hydrochloric acid (mass fraction 37.5%) was added to the obtained SiO2-TiO2 sol suspension, the pH value was adjusted to 2, and the stirring was continued for 6h, followed by the addition of 0.3g of hydroxymethyl cellulose (molecular weight 90000) and 0.1g of polyethylene glycol (molecular weight 400), 0.5g of potassium lignin sulfonate (molecular weight 5000-10000) and 1.5g of lignin sulfonate (molecular weight 20000), and the mixture was stirred until completely dissolved. The obtained sol mixed suspension was allowed to stand and age for 8.5 h, and the obtained mixed solution was recorded as L-SiO2-TiO2-ZrO2 sol mixed suspension; the ceramic membrane was placed in the obtained L-SiO2-TiO2-ZrO2 sol mixed suspension and soaked for 60 s, and then placed in a 35°C environment and dried for 3 days to obtain a L-SiO2-TiO2-ZrO2 sol composite ceramic nanofiltration membrane embryo; the obtained L-SiO2-TiO2-ZrO2 sol composite ceramic nanofiltration membrane embryo was placed in a tubular furnace in an atmosphere with an oxygen to nitrogen volume ratio of 0.8:9.2, and the temperature was raised to 650°C at 1°C / min and fired for 2 h to finally obtain a carbon-ceramic composite nanofiltration membrane.

[0073] Example 8

[0074] 4.3 g of tetraethyl orthosilicate, 8.7 g of tetrabutyl titanate, 6.1 g of zirconium n-butoxide, 40 g of n-butanol and 23 g of water were mixed and stirred for 3 h to hydrolyze to obtain a SiO2-TiO2-ZrO2 sol suspension; 0.21 g of acetic acid (mass fraction 99.5%) was added to the obtained SiO2-TiO2-ZrO2 sol suspension, the pH value was adjusted to 4, and the stirring was continued for 10 h, and then 1.4 g of polyvinyl pyrrolidone (molecular weight 58000) and 3.1 g of lignin acetate (molecular weight 15000-18000) were added and stirred until completely dissolved, and the obtained sol mixed suspension was allowed to stand for 1 hr. 6h, and the obtained mixed liquid is recorded as L-SiO2-TiO2-ZrO2 sol mixed suspension; the ceramic membrane is placed in the obtained L-SiO2-TiO2-ZrO2 sol mixed suspension and immersed for 140s, and then placed in a 40℃ environment and dried for 4 days to obtain a L-SiO2-TiO2-ZrO2 sol composite ceramic nanofiltration membrane embryo; the obtained L-SiO2-TiO2-ZrO2 sol composite ceramic nanofiltration membrane embryo is placed in a tubular furnace in an atmosphere with an oxygen to nitrogen volume ratio of 0.3:9.7, and the temperature is increased at 1℃ / min to 600℃ and fired for 2h to finally obtain a carbon-ceramic composite nanofiltration membrane.

[0075] Embodiment 9

[0076] 4.1 g of tetraethyl orthosilicate, 13.2 g of tetrabutyl titanate, 0.8 g of zirconium n-butoxide, 25 g of n-butanol and 22 g of water were mixed and stirred for 2.5 h to hydrolyze to obtain a SiO2-TiO2-ZrO2 sol suspension; 0.21 g of acetic acid (mass fraction 99.5%) was added to the obtained SiO2-TiO2-ZrO2 sol suspension, the pH value was adjusted to 5, and the stirring was continued for 8 h. Then, 1.6 g of polyvinyl pyrrolidone (molecular weight 58,000) and 2.1 g of lignin sulfonate (molecular weight 20,000) were added and stirred until completely dissolved. The obtained sol mixed suspension was allowed to stand and age for 14 h. The obtained mixed liquid is recorded as L-SiO2-TiO2-ZrO2 sol mixed suspension; the ceramic membrane is placed in the obtained L-SiO2-TiO2-ZrO2 sol mixed suspension and immersed for 110s, and then placed in a 50°C environment and dried for 2 days to obtain a L-SiO2-TiO2-ZrO2 sol composite ceramic nanofiltration membrane embryo; the obtained L-SiO2-TiO2-ZrO2 sol composite ceramic nanofiltration membrane embryo is placed in a tubular furnace in an atmosphere with an oxygen to nitrogen volume ratio of 0.4:9.6, and the temperature is raised to 600°C at 0.5°C / min and fired for 2h to finally obtain a carbon-ceramic composite nanofiltration membrane.

[0077] Comparative Example 1

[0078] 2.3g of tetraethyl orthosilicate, 5.6g of tetrabutyl titanate, 2.1g of zirconium n-butoxide, 33.2g of methanol and 20g of water were mixed, stirred for 3h, and hydrolyzed to obtain a SiO2-TiO2-ZrO2 sol suspension; 0.1g of hydrochloric acid (mass fraction 37.5%) was added to the obtained SiO2-TiO2-ZrO2 sol suspension, the pH value was adjusted to 4, and stirring was continued for 2h, and then 0.6g of hydroxymethyl cellulose (molecular weight 90000) was added and stirred until completely dissolved, and the obtained sol mixed suspension was allowed to stand and age for 12h; the ceramic membrane was placed in the aged SiO2-TiO2-ZrO2 sol mixed suspension and soaked for 40s, and then dried in a 40℃ environment for 3 days to obtain a SiO2-TiO2-ZrO2 sol ceramic nanofiltration membrane embryo. The obtained SiO2-TiO2-ZrO2 sol composite ceramic nanofiltration membrane embryo was placed in a tubular furnace, and in an atmosphere with an oxygen to nitrogen volume ratio of 0.3:9.7, the temperature was raised to 700°C at 2°C / min and fired for 3 hours to finally obtain a pure ceramic nanofiltration membrane.

[0079] Comparative Example 2

[0080] 0.6 g of hydroxymethyl cellulose (molecular weight 90,000), 0.4 g of eugenol, 0.4 g of potassium lignin sulfonate (molecular weight 5,000-10,000), and 0.4 g of lignin oxalate (molecular weight 30,000) were added to 20 g of water and stirred until completely dissolved to obtain a water-soluble lignin derivative mixed solution; a ceramic membrane was placed in the obtained solution and soaked for 40 seconds, and then dried in a 40°C environment for 3 days to obtain a nanofiltration membrane embryo with a lignin derivative layer; the obtained embryo was placed in a tubular furnace, and in an atmosphere with an oxygen to nitrogen volume ratio of 0.3:9.7, the temperature was raised to 700°C at 2°C / min and fired for 3 hours to finally obtain a carbon molecular sieve nanofiltration membrane.

[0081] Figure 1 The following are scanning electron microscope images of the carbon-ceramic composite nanofiltration membrane prepared in Example 3, the pure ceramic nanofiltration membrane prepared in Comparative Example 1, and the base membrane (ie, ceramic membrane) without any treatment. Figure 1 It can be seen that compared with Comparative Example 1 and the base membrane, the carbon-ceramic composite nanofiltration membrane prepared in Example 3 has a more complete and uniform microstructure and a smaller pore size (the membrane pore size is about 5 nm).

[0082] Figure 2 The carbon-ceramic composite nanofiltration membrane prepared in Example 3 ( Figure 2 Digital photos of the carbon-ceramic film in the film) and the base film without any treatment. Figure 2 It can be seen that the prepared nanofiltration membrane has a smooth and uniform morphology and is firmly bonded to the substrate.

[0083] Figure 3 The carbon-ceramic composite nanofiltration membrane prepared in Example 3 ( Figure 3 Digital photographs of the separation of cresol red sodium salt (concentration 40 mg / L) from an aqueous solution using a carbon-ceramic nanofiltration membrane, a pure ceramic nanofiltration membrane prepared in Comparative Example 1, a carbon molecular sieve nanofiltration membrane prepared in Comparative Example 2, and an untreated ceramic-based membrane. As can be seen, the prepared carbon-ceramic composite nanofiltration membrane has excellent separation efficiency for cresol red sodium salt (-400 Da).

[0084] Figure 4 The performance curves of the carbon-ceramic composite nanofiltration membrane prepared in Example 3, the pure ceramic nanofiltration membrane prepared in Comparative Example 1, and the carbon molecular sieve nanofiltration membrane prepared in Comparative Example 2 for separating MgSO4 (concentration 250 mg / L) in aqueous solution are shown. Figure 4 It can be seen that compared with the comparative example, the carbon-ceramic composite nanofiltration membrane prepared in Example 3 has excellent and balanced separation performance, with a MgSO4 rejection rate of 98.4% (Comparative Example 1: 85.7%) and a flux of 12.3LMH / bar (Comparative Example 2: 5.4LMH / bar). This shows that the carbon-ceramic composite method can balance the flux and retention performance of pure ceramic and carbon molecular sieve nanofiltration membranes. This composite nanofiltration membrane has great application prospects in the field of liquid separation, and is particularly suitable for use in the separation of small molecular weight pollutants.

[0085] The carbon-ceramic composite nanofiltration membranes prepared in Examples 1, 2, and 4 through 9 had a smooth and uniform morphology and were firmly bonded to the substrate. The carbon-ceramic composite nanofiltration membranes prepared in Examples 1, 2, and 4 through 9 were subjected to the same separation performance test (separating MgSO4 (concentration 250 mg / L) in an aqueous solution). The resulting carbon-ceramic composite nanofiltration membranes all exhibited high membrane flux and excellent retention performance, as shown in Table 1.

[0086] Table 1 Separation performance of carbon-ceramic composite nanofiltration membranes prepared in Example 1, Example 2, and Example 4 to Example 9

[0087] project Flux (LMH / bar) Retention rate (%) Example 1 10.15 98.37 Example 2 11.89 99.12 Example 4 10.75 98.88 Example 5 9.85 97.5 Example 6 12.3 99.6 Example 7 11.23 98.45 Example 8 10.99 99.01 Embodiment 9 12.15 97.85

[0088] The above description is merely a preferred embodiment of the present invention and does not constitute any limitation thereto. It should be noted that those skilled in the art may make various improvements and modifications without departing from the principles of the present invention, and such improvements and modifications shall also be considered within the scope of protection of the present invention.

Claims

1. A carbon-ceramic composite nanofiltration membrane, characterized in that: The preparation comprises the following raw materials in parts by weight: 5-30 parts of oxide precursor, 10-50 parts of alcohol solvent, 1-35 parts of water, 0.04-0.5 parts of acid catalyst, 0.1-2 parts of film-forming agent, 0.1-4 parts of water-soluble lignin derivative; The oxide precursors include a silicon oxide precursor, a titanium oxide precursor and a zirconium oxide precursor, the mass ratio of the silicon oxide precursor, the titanium oxide precursor and the zirconium oxide precursor is (0-10):(0-20):(0-9), and the masses of the silicon oxide precursor, the titanium oxide precursor and the zirconium oxide precursor are not 0.

2. The carbon-ceramic composite nanofiltration membrane according to claim 1, characterized in that: The mass ratio of the silicon oxide precursor, the titanium oxide precursor and the zirconium oxide precursor is (2-8.5):(2-15):(0.5-7).

3. The carbon-ceramic composite nanofiltration membrane according to claim 1 or 2, characterized in that: The silicon oxide precursor includes one or more of tetraethyl orthosilicate, tetramethyl orthosilicate, silica sol and sodium silicate; the titanium oxide precursor includes one or more of tetrabutyl titanate, tetraethyl titanate, tetraisopropyl titanate and titanium tetrachloride; the zirconium oxide precursor includes one or more of zirconium n-butoxide, tetrabutyl zirconate, zirconium oxychloride and zirconium sulfate.

4. The carbon-ceramic composite nanofiltration membrane according to claim 1, characterized in that: The alcohol solvent includes one or more of methanol, ethanol, isopropanol and n-butanol.

5. The carbon-ceramic composite nanofiltration membrane according to claim 1, characterized in that: The acid catalyst includes one or more of acetic acid, hydrochloric acid, nitric acid and benzoic acid.

6. The carbon-ceramic composite nanofiltration membrane according to claim 1, characterized in that: The film-forming agent includes one or more of hydroxymethyl cellulose, polyvinyl alcohol, polyethylene glycol and polyvinyl pyrrolidone.

7. The carbon-ceramic composite nanofiltration membrane according to claim 1, characterized in that: The water-soluble lignin derivatives include one or more of lignin phenol, lignin sulfonate and lignin acid ester; the lignin phenol includes one or more of guaiacol, syringol and catechol; the lignin sulfonate includes sodium lignin sulfonate and / or potassium lignin sulfonate; the lignin acid ester includes one or more of lignin sulfonate, lignin acetate and lignin oxalate.

8. The method for preparing the carbon-ceramic composite nanofiltration membrane according to any one of claims 1 to 7, characterized in that: The following steps are involved: The oxide precursor, alcohol solvent and water are mixed to undergo a hydrolysis reaction to obtain a SiO2-TiO2-ZrO2 sol suspension; The SiO2-TiO2-ZrO2 sol suspension is mixed with an acid catalyst to carry out a polycondensation reaction, and the obtained polycondensation reaction liquid is mixed with a film-forming agent and a water-soluble lignin derivative and aged to obtain a sol mixed suspension; forming a film of the sol mixed suspension on a base membrane and then drying the film to obtain a sol composite ceramic nanofiltration membrane embryo; The sol-composite ceramic nanofiltration membrane embryo is sintered to obtain the carbon-ceramic composite nanofiltration membrane.

9. The preparation method according to claim 8, characterized in that The hydrolysis reaction time is 1 to 5 hours; the polycondensation reaction time is 1 to 12 hours; the aging time is 5 to 24 hours; the sintering temperature is 300 to 1000°C and the time is 1 to 10 hours, and the sintering atmosphere includes oxygen and nitrogen, and the volume ratio of oxygen to nitrogen is (0 to 2): (8 to 10).

10. Use of the carbon-ceramic composite nanofiltration membrane according to any one of claims 1 to 7 or the carbon-ceramic composite nanofiltration membrane prepared by the preparation method according to claim 8 or 9 in liquid separation or water pollutant treatment.